American politics : ideals and realities - McKenna, George (New York : McGraw Hill Education, 1976)
This book is an attempt to analyze American political institutions and processes from the standpoint of the old liberal ideas, which, I am convinced, can provide a more realistic framework for analysis than much of what has passed for realism over the past century.
Part One. Prerequisites for democracy -- Part Two. Processes of democracy -- Part Three. Components of american democracy.
Includes index.
Keywords: UNITED STATES -- POLITICS AND GOVERNMENT -- HANDBOOKS, MANUALS, ETC